Structure, waveguide, optical modulator, and method for manufacturing structure

By forming a seed layer and a ferroelectric thin film on an amorphous material substrate, the problem of insufficient electro-optic effect in the prior art is solved, and a ferroelectric thin film with high electro-optic effect is realized, which supports the manufacturing of high-speed optical modulators and meets the requirements of miniaturization and power saving.

CN121002433APending Publication Date: 2025-11-21KYUSHU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480010962.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-14
Filing Date
2024-02-14
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing technologies make it difficult to form ferroelectric thin films with high electro-optic effects on substrates made of amorphous materials, resulting in slow electro-optic switching speeds of optical control elements, which cannot meet the requirements of miniaturization, wide bandwidth and power saving.

Method used

A seed layer is formed on a substrate made of amorphous material, and a PZT, PLZT, BTO or BSTO thin film is deposited on it. The light propagation loss is ensured to be below 1 dB/mm by measurement method. A ferroelectric thin film is formed by hydrophilic polymer coating and sol-gel method, and the composition and thickness of the seed layer are optimized.

Benefits of technology

This technology enables the efficient formation of ferroelectric thin films with excellent electro-optic effects on amorphous material substrates, reducing the operating voltage of optical modulators, improving the electro-optic coefficient and modulation speed, and supporting the fabrication of high-speed optical modulators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121002433A_ABST
    Figure CN121002433A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to form a ferroelectric thin film, which exhibits a high electro-optical effect, on a substrate comprising an amorphous material. The present invention pertains to a structure (10) having a substrate (2) comprising an amorphous material, a seed layer (4) laminated on the substrate (2), and a PZT thin film, PLZT thin film, BTO thin film or BSTO thin film (6) laminated on the seed layer (4), the structure (10) being characterized in that the light propagation loss is 1 db / mm or less when the light propagation loss is calculated by a predetermined measurement method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to structures, waveguides, optical modulators, and methods for manufacturing structures. Background Technology

[0002] PZT (lead zirconate titanate), PLZT (lanthanum lead zirconate titanate), BTO (barium titanate), and BSTO (barium strontium titanate) are piezoelectric ceramics with a wide range of applications. PZT, PLZT, BTO, and BSTO are known to have high polarization, thus exhibiting a large electro-optic effect. They can switch the phase of light by switching on and off the applied voltage, making them suitable for use as optical control elements such as optical shutters. Such optical control elements are used, for example, in fiber optic communication systems.

[0003] Previously, bulk PZT and similar materials were used in optical control components, but in recent years there has been a demand for further miniaturization, bandwidth reduction, and power saving in optical control components. Furthermore, to meet these requirements, research is underway on forming ferroelectric thin films such as PZT on substrates and applying them to optical control components (e.g., Patent Documents 1 and 2). These documents disclose structures including a substrate and a ferroelectric thin film such as PZT formed on the substrate. Patent Document 1 discloses a process of forming PLZT by spin-coating a metal alkoxide layer after forming a seed layer on a silicon substrate, and studies the use of Ti ultrafine powder as particles for forming the seed layer. Additionally, Patent Document 2 discloses a device in which a spinel layer is formed on a silicon substrate, and then a PLZT thin film is formed thereon.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Publication No. 2005 / 015292

[0007] Patent Document 2: Japanese Patent Application Publication No. 63-221306 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] Previously, special substrates such as sapphire with crystal orientation were used to form ferroelectric thin films such as PZT on substrates and promote crystal growth. However, sapphire has a high dielectric constant, resulting in slow electro-optic switching speeds and limiting its applications. Therefore, research is underway on forming ferroelectric thin films such as PZT on substrates made of amorphous materials, such as silicon substrates with thermal oxide films. However, in existing technologies, it is not possible to form ferroelectric thin films exhibiting high electro-optic effects on substrates made of amorphous materials, and further technological development is anticipated.

[0010] Therefore, in order to solve the problem of this prior art, the inventors conducted research with the aim of forming a ferroelectric thin film with a high electro-optic effect on a substrate made of an amorphous material.

[0011] Methods for solving problems

[0012] The following are examples of specific embodiments of the present invention.

[0013] [1] A structure having:

[0014] A substrate made of amorphous material;

[0015] Seed layer deposited on substrate; and

[0016] PZT thin films, PLZT thin films, BTO thin films, or BSTO thin films deposited on a seed layer

[0017] in,

[0018] When the light propagation loss is calculated using the following measurement method, the light propagation loss is less than 1 dB / mm.

[0019] (Determination Method)

[0020] Waveguide patterns with ridge lengths of 2mm, 4mm, 6mm, and 8mm, ridge height of 100nm, and ridge width of 3μm were formed on the structure. A 1μm thick upper cladding layer of polymethyl methacrylate resin was formed on the waveguide pattern to serve as the waveguide. A laser source with a wavelength of 1550nm and an optical fiber were used to input laser light into the waveguide end face. The laser light emitted from the opposite side of the waveguide was focused using an objective lens, and the light intensity was measured using an optical power meter. The input laser intensity was fixed at 10dBm. The ratio of the output laser intensity to the input laser intensity in waveguides with different waveguide lengths (input-output loss) was calculated. The slope of the input-output loss relative to the waveguide length was calculated as the optical propagation loss.

[0021] [2] According to the structure described in [1], the seed layer contains lanthanum nitrate as the main component.

[0022] [3] A structure having:

[0023] A substrate made of amorphous material;

[0024] Seed layer deposited on substrate; and

[0025] PZT thin films, PLZT thin films, BTO thin films, or BSTO thin films deposited on a seed layer

[0026] The seed layer contains lanthanum nitrate as the main component.

[0027] [4] The structure according to any one of [1] to [3], wherein the thickness of the seed layer is less than 15 nm.

[0028] [5] The structure according to any one of [1] to [4], wherein the substrate is a silicon substrate.

[0029] [6] According to the structure described in [5], the silicon substrate has a thermal oxide film.

[0030] [7] The structure according to technical solution 1 or 3, wherein the PZT film, PLZT film, BTO film or BSTO film deposited on the seed layer also has a PZT film, PLZT film, BTO film or BSTO film.

[0031] [8] A waveguide comprising any one of the structures described in [1] to [7].

[0032] [9] An optical modulator is formed by forming electrodes in any one of the structures described in [1] to [7].

[0033]

[10] A method for manufacturing a structure, which is a method for manufacturing the structure described in any one of [1] to [7], comprising:

[0034] The process of forming a seed layer on a substrate made of an amorphous material; and

[0035] The process of forming PZT thin films, PLZT thin films, BTO thin films or BSTO thin films on a seed layer.

[0036]

[11] The method for manufacturing the structure according to

[10] further includes, before the step of forming the seed layer, a step of coating a hydrophilic polymer content on the substrate.

[0037]

[12] A method for manufacturing a structure, comprising:

[0038] The process of coating a hydrophilic polymer onto a substrate made of an amorphous material;

[0039] The process of forming a seed layer on a substrate surface coated with a hydrophilic polymer inclusion; and

[0040] The process of forming PZT thin films, PLZT thin films, BTO thin films or BSTO thin films on a seed layer.

[0041]

[13] The method for manufacturing the structure according to any one of

[10] to

[12] , wherein the seed layer contains lanthanum nitrate as the main component.

[0042]

[14] The method of manufacturing the structure according to

[11] or

[12] , wherein the hydrophilic polymer is polyvinylpyrrolidone.

[0043]

[15] The method for manufacturing the structure according to any one of

[10] to

[14] , wherein the PZT film, PLZT film, BTO film or BSTO film is formed by sol-gel method.

[0044]

[16] The method for manufacturing a structure according to any one of

[10] to

[15] , wherein the substrate is a silicon substrate.

[0045] Invention Effects

[0046] According to the present invention, a ferroelectric thin film exhibiting high electro-optic effect can be formed on a substrate made of an amorphous material. This enables the provision of waveguides, optical modulators, and the like with excellent electro-optic effects. Attached Figure Description

[0047] Figure 1 It is a cross-sectional diagram illustrating the structure of the structure.

[0048] Figure 2 It is a cross-sectional diagram illustrating the structure of the waveguide.

[0049] Figure 3 This is a schematic diagram illustrating the process of forming a waveguide.

[0050] Figure 4 This is a top view illustrating the structure of the waveguide.

[0051] Figure 5 It is a graph that plots the input and output losses relative to the length of each waveguide.

[0052] Figure 6 This is a top view illustrating the structure of an optical modulator.

[0053] Figure 7 This is a photograph of the PLZT film obtained in Comparative Example 1. Figure 7 (b) is Figure 7 Enlarged photograph of the area enclosed by the dashed line in (a).

[0054] Figure 8 The results are from analyzing the optical modulation characteristics of the optical modulator using an oscilloscope.

[0055] Figure 9 This is a top view illustrating the structure of an optical modulator.

[0056] Figure 10 This is the result of measuring the eye diagram of the optically modulated signal.

[0057] Figure 11It is the XRD diffraction pattern of the PZT film.

[0058] Figure 12 It is the XRD diffraction pattern of the PLZT film.

[0059] Figure 13 It is the XRD diffraction pattern of the BTO film.

[0060] Figure 14 It is the XRD diffraction pattern of the BTO film. Detailed Implementation

[0061] The present invention will now be described in detail. The descriptions of the technical features described below are sometimes based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. It should be noted that the numerical range indicated by “~” in this specification refers to the range including the values ​​described before and after “~” as the lower and upper limits.

[0062] (Structure)

[0063] The first embodiment of the present invention relates to a structure comprising: a substrate made of an amorphous material; a seed layer deposited on the substrate; and a PZT thin film, PLZT thin film, BTO thin film, or BSTO thin film (hereinafter, these films are also collectively referred to as ferroelectric thin films) deposited on the seed layer. Furthermore, in the first embodiment, the light propagation loss is 1 dB / mm or less when the light propagation loss is calculated by the following measurement method.

[0064] (Determination Method)

[0065] Waveguide patterns with ridge lengths of 2mm, 4mm, 6mm, and 8mm, a ridge height of 100nm, and a ridge width of 3μm were formed on the aforementioned structure. A 1μm thick upper cladding layer of polymethyl methacrylate resin was formed on the waveguide pattern to serve as the waveguide. A 1550nm wavelength laser source and optical fiber were used to input laser light into the waveguide end face. An objective lens was used to focus the laser light emitted from the opposite side of the waveguide, and the light intensity was measured using an optical power meter. The input laser intensity was fixed at 10dBm. The ratio of the output laser intensity to the input laser intensity (input-output loss) in waveguides of different lengths was calculated, and the slope of the input-output loss relative to the waveguide length was calculated as the optical propagation loss.

[0066] In the first embodiment, when the optical propagation loss of the waveguide including the structure is calculated by the above-described measurement method, the optical propagation loss is preferably 0.9 dB / mm or less, more preferably 0.8 dB / mm or less, even more preferably 0.7 dB / mm or less, and particularly preferably 0.6 dB / mm or less. It should be noted that the lower limit of the optical propagation loss is not particularly limited, and may also be 0.01 dB / mm.

[0067] The second embodiment of the present invention relates to a structure having: a substrate made of an amorphous material; a seed layer deposited on the substrate; and a PZT film, PLZT film, BTO film or BSTO film (hereinafter, these films are also collectively referred to as ferroelectric films) deposited on the seed layer, wherein the seed layer contains lanthanum nitrate as a main component.

[0068] Figure 1 This is a cross-sectional view illustrating the structure of the structure in the first and second embodiments. For example... Figure 1 As shown, the structure 10 in this embodiment sequentially comprises a substrate 2, a seed layer 4, and a ferroelectric thin film 6. It should be noted that other layers may also be provided between each layer, but it is preferable that the substrate 2 and the seed layer 4 are directly laminated, and it is also preferable that the seed layer 4 and the ferroelectric thin film 6 are directly laminated.

[0069] This embodiment, having the above-described configuration, enables the formation of a ferroelectric thin film exhibiting a high electro-optic effect on a substrate made of an amorphous material. Specifically, in this embodiment, when a light modulator including a structure (phase length (electrode length): 4 mm) is fabricated using the method described in the examples, and half-wavelength voltage is evaluated using laser light sources with wavelengths of 1550 nm and 1310 nm, the electro-optic coefficient is preferably 50 pm / V or higher, more preferably 60 pm / V or higher, further preferably 70 pm / V or higher, and particularly preferably 80 pm / V or higher. If the electro-optic coefficient is within the above range, the ferroelectric thin film can be evaluated as having a high electro-optic effect.

[0070] In this embodiment, the electro-optic coefficient was calculated using laser light sources with wavelengths of 1550 nm and 1310 nm to measure the half-wavelength voltage (Vπ). The half-wavelength voltage (Vπ) is one of the indicators representing the operating voltage of the optical modulator; it is defined as the voltage required for a 180° electro-optic phase shift. The electro-optic coefficient was calculated using the following formula.

[0071] r=λ×d / (n 3 ×Vπ×L×Γ)

[0072] In the above formula, r represents the electro-optic coefficient, λ represents the wavelength of the laser source, d represents the electrode spacing, n represents the effective refractive index of the waveguide, Vπ represents the half-wavelength voltage, L represents the electrode length, and Γ represents the overlap between the light and the electric field in the waveguide.

[0073] When using a laser source with a wavelength of 1550 nm, the half-wavelength voltage (Vπ) of the optical modulator is preferably 5V or less, more preferably 2V or less, and even more preferably 1V or less. It should be noted that the lower limit of the half-wavelength voltage (Vπ) is not particularly limited, but is preferably 0.0001V or more.

[0074] When using a laser source with a wavelength of 1310 nm, the half-wavelength voltage (Vp) of the optical modulator is preferably 5V or less, more preferably 2V or less, and even more preferably 1V or less. It should be noted that the lower limit of the half-wavelength voltage (Vπ) is not particularly limited, but is preferably 0.0001V or more.

[0075] It should be noted that the half-wavelength voltage is inversely proportional to the phase length. Therefore, as an indicator of the half-wavelength voltage characteristic relative to the phase length, there is the VπL value, which is obtained by multiplying the half-wavelength voltage by the phase length. When measuring the optical modulator using a laser source with a wavelength of 1550 nm, the VπL value is preferably 2 Vcm or less, more preferably 1 Vcm or less, and even more preferably 0.5 Vcm or less. Furthermore, the VπL value is preferably 0.0001 Vcm or more.

[0076] When using a laser light source with a wavelength of 1310 nm, the VπL value of the optical modulator is preferably 2 Vcm or less, more preferably 1 Vcm or less, and even more preferably 0.5 Vcm or less. Furthermore, the VπL value is preferably 0.0001 Vcm or more.

[0077] In this embodiment, a large electro-optic coefficient can be obtained in the optical modulator, thus enabling the fabrication of an optical modulator capable of high-speed operation. For example, when fabricating an optical modulator using the structure of this embodiment, optical modulation speeds of 40 Gbit / s or higher, 50 Gbit / s or higher, 60 Gbit / s or higher, 70 Gbit / s or higher, 80 Gbit / s or higher, 90 Gbit / s or higher, and even 100 Gbit / s or higher can be achieved. It should be noted that the accuracy of the optical modulation signal can be evaluated by the shape of the eye diagram of the optical modulation signal and the Q value defined by the signal amplitude and signal noise. For example, the Q value defined by the signal amplitude and signal noise is preferably 3.5 or higher, more preferably 4.0 or higher, further preferably 4.5 or higher, and particularly preferably 5.0 or higher.

[0078] The structure of this embodiment is preferably manufactured using the manufacturing processes described later. Specifically, the structure of this embodiment is preferably manufactured by forming a hydrophilic polymer coating (film) on a substrate made of an amorphous material, followed by a process of forming a seed layer, and then forming a ferroelectric thin film on the seed layer. While it is assumed that the hydrophilic polymer coating (film) burns out during the firing process, the structure of this embodiment may also contain components from the hydrophilic polymer coating (film). For example, components or elements from the hydrophilic polymer may exist between the substrate and the seed layer.

[0079] For example, lanthanum nitrate used in seed layers is prone to microcrystallization during heating, making it difficult to form a dense and uniform seed layer. That is, it is difficult to uniformly crystallize the ferroelectric thin film on the seed layer. On the other hand, hydrophilic polymers can form a uniform film on a substrate made of amorphous materials. Therefore, it is possible to connect the microcrystals in a way that prevents lanthanum nitrate from becoming non-uniform during heating, thereby densifying the seed layer. It should be noted that the hydrophilic polymer burns up during the final high-temperature sintering process, but lanthanum nitrate remains at 300–400°C during crystallization; therefore, components originating from the hydrophilic polymer can be detected depending on the sintering conditions.

[0080] Alternatively, this embodiment can also be a structure manufactured by a process of forming a seed layer by coating a seed layer solution containing a hydrophilic polymer and lanthanum nitrate onto a substrate made of an amorphous material, and then forming a ferroelectric thin film on the seed layer. In this case, the layers may contain components and elements derived from the hydrophilic polymer.

[0081] <Substrate>

[0082] The structure of this embodiment has a substrate made of an amorphous material. Examples of amorphous materials include glass, silicon, silicon oxide, silicon nitride, titanium oxide, and ITO. Among these, silicon is preferred, specifically amorphous silicon.

[0083] Substrates made of amorphous materials lack crystalline orientation, making it difficult to form ferroelectric thin films such as PZT on them. However, according to this embodiment, ferroelectric thin films such as PZT can be formed on substrates made of amorphous materials. Furthermore, by using a substrate made of amorphous materials, miniaturization of the structure becomes easier, facilitating the integration of various components onto the silicon substrate. Therefore, in this embodiment, for example, when the structure is used in an optical modulator, the operating voltage can be reduced, thereby enabling the manufacture of a high-speed optical modulator at low cost.

[0084] The substrate made of amorphous material used in this embodiment is preferably a silicon substrate, and the silicon substrate preferably has a thermally oxidized film (e.g., a SiO2 film). In this case, the thickness of the Si substrate in the silicon substrate (SiO2 / Si substrate) with the thermally oxidized film is preferably 100 μm or more, more preferably 200 μm or more, further preferably 300 μm or more, and particularly preferably 500 μm or more. Furthermore, the thickness of the Si substrate is preferably 1 mm or less. The thickness of the SiO2 film in the silicon substrate (SiO2 / Si substrate) with the thermally oxidized film is preferably 1 μm or more, more preferably 2 μm or more, and further preferably 3 μm or more. Furthermore, the thickness of the SiO2 film is preferably 100 μm or less.

[0085] <Seed Layer>

[0086] The structure of this embodiment has a seed layer deposited on a substrate. In this embodiment, by having a seed layer in the structure, crystals constituting ferroelectric thin films can be grown on a substrate made of an amorphous material. Furthermore, by having a seed layer in the structure, ferroelectric thin films with excellent crystal orientation can be formed.

[0087] In this embodiment, the seed layer preferably contains lanthanum nitrate as the main component. By forming a seed layer containing lanthanum nitrate as the main component, it is easy to form a uniform ferroelectric thin film with good crystal orientation.

[0088] The content of lanthanum nitrate relative to the total mass of the seed layer is 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. It should be noted that the content of lanthanum nitrate relative to the total mass of the seed layer can be 100% by mass.

[0089] The thickness of the seed layer is preferably 1 nm or more, more preferably 2 nm or more, and even more preferably 3 nm or more. Furthermore, the thickness of the seed layer is preferably 30 nm or less, more preferably 25 nm or less, even more preferably 20 nm or less, and particularly preferably 15 nm or less. By keeping the thickness of the seed layer within the above ranges, it is easier to form a uniform ferroelectric thin film with good crystal orientation.

[0090] In this embodiment, a relatively large-area homogeneous seed layer can be formed. For example, a seed layer with a generally uniform thickness, free of cracks and gaps, measuring 0.5 × 0.5 cm, can be formed. 2 The above can form a 1.0×1.0cm 2 The above can form a 2.0×2.0cm 2 above.

[0091] <Ferroelectric Thin Films>

[0092] The structure of this embodiment has a ferroelectric thin film on a seed layer. The seed layer and the ferroelectric thin film are preferably directly laminated, but other layers can also be disposed between the seed layer and the ferroelectric thin film. Here, the ferroelectric thin film is preferably a film composed of perovskite-structured oxides, preferably PZT (lead zirconate titanate) film, PLZT (lanthanum lead zirconate titanate) film, BTO (barium titanate) film, or BSTO (strontium barium titanate) film. Among these, PZT film or PLZT film is preferred. Especially when using PZT film or PLZT film, a larger electro-optic coefficient (electro-optic effect) can be achieved compared to using lithium niobate film. Furthermore, PZT and PLZT are ferroelectric materials, and their polarization change is proportional to the magnitude of the electric field. Therefore, the voltage required for electro-optic modulation and switching can be reduced. In addition, due to the rapid polarization change, the speed of optical modulation and switching can be accelerated.

[0093] PZT and PLZT are represented by the following structural formulas, respectively.

[0094] PZT: PbZr x Ti 1-x O3

[0095] PLZT: Pb 1-x La x Zr 1-y Ti y O3 (O≤x<1, O≤y<1)PLZT replaces a portion of the lead in PZT with lanthanum. Alternatively, in this embodiment, materials in which Mn (manganese), Mg (magnesium), Nb (niobium), Co (cobalt), Fe (iron), Ni (nickel), Zn (zinc), Al (aluminum), Ta (tantalum), W (tungsten), etc., are added to PZT or PLZT can also be used.

[0096] The thickness of the ferroelectric thin film is preferably 100 nm or more, more preferably 200 nm or more, and even more preferably 400 nm or more. Furthermore, the thickness of the ferroelectric thin film is preferably 5 μm or less. By making the ferroelectric thin film within the above-mentioned range and depositing it on a silicon substrate with an oxide film, the effective dielectric constant can be reduced, and the modulation speed can be increased.

[0097] The grain size of the crystals contained in the ferroelectric thin film is preferably below the wavelength of the light used in optical modulation or switching, for example, preferably below 100 nm. Furthermore, in the ferroelectric thin film, it is preferable that the grains are densely aggregated in a light-non-scattering manner.

[0098] The crystal structure of the crystal contained in the ferroelectric thin film preferably has only (100) diffraction peaks and (200) diffraction peaks that indicate crystal orientation, and the crystal state with small half width of each peak has the highest and best orientation.

[0099] The structure of this embodiment can also have a structure in which a ferroelectric thin film is further deposited on the aforementioned ferroelectric thin film. That is, the structure of this embodiment can have a first ferroelectric thin film and a second ferroelectric thin film on the seed layer. In this case, the first ferroelectric thin film is preferably a PZT thin film, a PLZT thin film, a BTO thin film, or a BSTO thin film, and more preferably a PZT thin film or a PLZT thin film. In addition, the second ferroelectric thin film is preferably a PZT thin film, a PLZT thin film, a BTO thin film, or a BSTO thin film, and more preferably a BTO thin film or a BSTO thin film. By forming the second ferroelectric thin film on the first ferroelectric thin film, crystal growth is easily promoted even if the second ferroelectric thin film is a ferroelectric thin film with a lattice size different from that of the seed layer.

[0100] When the first ferroelectric thin film and the second ferroelectric thin film are formed on the seed layer, their combined film thickness is preferably 100 nm or more, more preferably 200 nm or more, and even more preferably 400 nm or more. Furthermore, the combined film thickness of the first ferroelectric thin film and the second ferroelectric thin film is preferably 5 μm or less.

[0101] <Uses of Structures>

[0102] The application of the structure in this embodiment is not particularly limited. For example, the structure can be used as an optical element, optical intensity modulator, optical phase modulator, directional coupler, ring resonator, optical switch element, beam steering element, multimode interference element, variable wavelength filter, variable optical intensity filter, etc. The structure in this embodiment exhibits excellent electro-optic effects, and is therefore particularly preferred as a component of optical elements and optical control devices, for example, particularly preferred as a component of waveguides, optical modulators, optical integrated circuits, optical switch circuits, etc.

[0103] (Manufacturing method of the structure)

[0104] The third embodiment of the present invention relates to a method for manufacturing a structure, which is a method for manufacturing the structure described in the first or second embodiment above. The method includes: a step of forming a seed layer on a substrate made of an amorphous material; and a step of forming a PZT film, PLZT film, BTO film, or BSTO film on the seed layer. In the manufacturing method of the third embodiment, prior to the step of forming the seed layer, it is preferable to further include a step of coating a hydrophilic polymer-containing material onto the substrate.

[0105] The fourth embodiment of the present invention relates to a method for manufacturing a structure, comprising: a step of coating a hydrophilic polymer inclusion on a substrate made of an amorphous material; a step of forming a seed layer on the surface of the substrate coated with the hydrophilic polymer inclusion; and a step of forming a PZT film, PLZT film, BTO film or BSTO film on the seed layer.

[0106] In this embodiment, the seed layer preferably contains lanthanum nitrate as a main component. The content of lanthanum nitrate relative to the total mass of the seed layer is 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. It should be noted that the content of lanthanum nitrate relative to the total mass of the seed layer can be 100% by mass.

[0107] In this embodiment, the process of coating a hydrophilic polymer onto a substrate made of an amorphous material is preferably included. Here, the hydrophilic polymer is preferably a nonionic hydrophilic polymer. Examples of such hydrophilic polymers include polyvinylpyrrolidone, polyvinyl alcohol, polyvinylamide, polyacrylamide, polyacrylic acid, polyethylene oxide, and polyamine. Among these, polyvinylpyrrolidone is particularly preferred.

[0108] The weight molecular weight of the hydrophilic polymer is not particularly limited, but is preferably in the range of 1,000 to 100,000.

[0109] In the process of coating a hydrophilic polymer inclusion onto a substrate, the hydrophilic polymer inclusion (a solution containing hydrophilic polymers) is coated onto the substrate. The coating method is not particularly limited and can be, for example, spin coating, dip coating, LSMCD (Liquid Source Misted Chemical Deposition), electrostatic spraying, etc. Spin coating is preferred. In this case, the concentration of the hydrophilic polymer in the hydrophilic polymer inclusion (the solution containing hydrophilic polymers) is preferably 0.001% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more. Furthermore, the concentration of the hydrophilic polymer is preferably 50% by mass or less, more preferably 10% by mass or less, even more preferably 2% by mass or less, and particularly preferably 1% by mass or less.

[0110] The hydrophilic polymer content (a solution containing a hydrophilic polymer) preferably includes a solvent in addition to the hydrophilic polymer. Examples of solvents include 2-methoxyethanol, butanol, ethanol, isopropanol, methanol, and water.

[0111] A hydrophilic polymer coating (film) is formed on a substrate by coating a hydrophilic polymer content onto the substrate. The thickness of the coating (film) is preferably, for example, 10 nm or less.

[0112] Alternatively, a drying process can be performed after coating the substrate with a hydrophilic polymer. In this case, the drying temperature is preferably 50–300°C, and the drying time is preferably 1 second to 10 minutes. Alternatively, a substrate cleaning process can be performed before coating the substrate with the hydrophilic polymer. In this case, a heating and drying process can be performed after cleaning.

[0113] In the process of forming the seed layer, a seed layer solution is coated onto a substrate or a hydrophilic polymer coating film. The coating method is not particularly limited and can include, for example, spin coating, dip coating, LSMCD (Liquid Source Misted Chemical Deposition), electrostatic spraying, etc. Spin coating is preferred. In this case, the concentration of seed particles in the seed layer solution is preferably 0.001% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.5% by mass or more. Furthermore, the concentration of seed particles is preferably 50% by mass or less, more preferably 10% by mass or less, and even more preferably 3% by mass or less.

[0114] The seed layer solution preferably contains a solvent that disperses the seed particles. Examples of solvents include 2-methoxyethanol, butanol, ethanol, isopropanol, methanol, and water.

[0115] It should be noted that, in the third embodiment, during the process of forming a seed layer on a substrate made of an amorphous material, the aforementioned hydrophilic polymer can be mixed into the seed layer solution. In this case, a seed layer solution containing the hydrophilic polymer is coated onto the substrate made of an amorphous material. Furthermore, in the fourth embodiment, the aforementioned hydrophilic polymer may also be included in the seed layer solution.

[0116] In the process of forming the seed layer, it is preferable to perform a firing (drying) step after applying the seed layer solution. The firing (drying) temperature is preferably 150–500°C, and the drying time is preferably 1–10 minutes. By performing such a drying step, the solvent can be removed.

[0117] In this embodiment, a seed layer formation step can be performed after each step of coating a hydrophilic polymer inclusion onto the substrate, but multiple steps of coating a hydrophilic polymer inclusion and / or forming a seed layer can also be performed separately. For example, the manufacturing method of the structure in this embodiment may include: a step of coating a hydrophilic polymer inclusion onto a substrate made of an amorphous material; a step of forming a seed layer on the surface of the substrate coated with the hydrophilic polymer inclusion; a step of coating a hydrophilic polymer inclusion onto the seed layer; a step of forming a seed layer on the surface of the seed layer coated with the hydrophilic polymer inclusion; and a step of forming a PZT film, PLZT film, BTO film, or BSTO film on the seed layer.

[0118] After the process of forming the seed layer, a firing process for crystallizing the seed layer can be provided. The firing temperature in the firing process is preferably 400°C or higher, more preferably 450°C or higher, and even more preferably 500°C or higher. Furthermore, the firing temperature in the firing process is preferably 700°C or lower, more preferably 650°C or lower, even more preferably 600°C or lower, and particularly preferably 550°C or lower. It should be noted that the firing time in the firing process is preferably 1 to 10 minutes. By keeping the firing temperature in the firing process within the above range, the crystal growth properties of the ferroelectric thin film are good. More specifically, the crystal structure of the ferroelectric thin film can be such that it has a c-axis in the direction normal to the substrate.

[0119] It should be noted that the coating (film) containing hydrophilic polymers is assumed to burn up during the aforementioned firing process. Therefore, it is difficult to analyze the presence of the coating (film) containing hydrophilic polymers in the structure of this embodiment. However, by forming a coating (film) containing hydrophilic polymers during the manufacturing process of the structure, a seed layer containing lanthanum nitrate can be formed on a substrate made of amorphous material, and a ferroelectric thin film with excellent crystal orientation can be formed on such a seed layer.

[0120] In the process of forming a PZT film, PLZT film, BTO film, or BSTO film on a seed layer, it is preferable to form a ferroelectric film on the seed layer using a sol-gel method. Specifically, a sol-gel solution for forming a ferroelectric film is coated onto the seed layer. The coating method is not particularly limited and can be, for example, spin coating, dip coating, LSMCD (Liquid Source Misted Chemical Deposition), electrostatic spraying, etc. Spin coating is preferred. In the process of forming the ferroelectric film, the above coating process can be repeated until a specified film thickness is achieved. In this embodiment, for example, the above coating process can be repeated 2 to 30 times. A heat treatment process can also be provided between each coating process. In this case, the heat treatment temperature is preferably 150 to 500°C, and the heat treatment time is preferably 1 to 10 minutes.

[0121] After the coating process, heat treatment is preferably performed in air or an O2 atmosphere to crystallize the ferroelectric material, and heat treatment in an O2 atmosphere is particularly preferred. The heat treatment temperature is preferably 400°C or higher, more preferably 450°C or higher, further preferably 500°C or higher, and particularly preferably 550°C or higher. Furthermore, the heat treatment temperature is preferably 800°C or lower, more preferably 750°C or lower, further preferably 700°C or lower, and particularly preferably 650°C or lower. It should be noted that the heat treatment time is preferably 1 to 30 minutes, more preferably 1 to 20 minutes, and further preferably 1 to 10 minutes. By keeping the heat treatment temperature within the above range, the crystal growth of the ferroelectric thin film is good. More specifically, the crystal structure of the ferroelectric thin film can be such that it has a c-axis in the direction normal to the substrate.

[0122] In the process of forming a ferroelectric thin film, a process of forming a second ferroelectric thin film may be further provided after the formation of the first ferroelectric thin film. In this case, it is preferable to provide the following process: forming the first ferroelectric thin film, performing heat treatment to crystallize the ferroelectric material, and then forming the second ferroelectric thin film.

[0123] (waveguide)

[0124] This embodiment relates to a waveguide (optical waveguide) that includes the above-described structure. In this embodiment, the waveguide can be a phase-modulated waveguide or a Mach-Zehnder interferometer waveguide.

[0125] The waveguide in this embodiment may, for example, have Figure 2 The structure shown. Figure 2 This is a cross-sectional view of the waveguide along its width (a cross-sectional view perpendicular to the direction in which the waveguide pattern extends). For example... Figure 2As shown, the waveguide 15 sequentially comprises a substrate 2, a seed layer 4, and a ferroelectric thin film 6, with ridges (protrusions) 14 formed on the ferroelectric thin film 6. Furthermore, the surface containing the ridges 14 is covered by a top cladding layer 8. Examples of materials constituting the top cladding layer 8 include acrylic resins such as polymethyl methacrylate (PMMA), epoxy resins, and silicon dioxide.

[0126] Figure 3 This is a schematic diagram illustrating the process of forming waveguide 15. For example... Figure 3 As shown, a waveguide resist pattern is fabricated on the ferroelectric thin film 6 of structure 10. Figure 3 (b)). Next, the ridge is formed by an etching process to remove the resist used in the waveguide. Figure 3 (c)). Then, waveguide 15 is obtained by forming the top cladding 8. Figure 3 (d) The maximum thickness of the top cladding 8 is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 3 μm or more. In addition, the maximum thickness of the top cladding 8 is preferably 100 μm or less.

[0127] The ridge length (waveguide length) of waveguide 15 is preferably 10 mm or less, more preferably 5 mm or less. The ridge length is preferably 0.001 mm or more.

[0128] The ridge height (waveguide height) is preferably less than 1 μm. The ridge height is preferably more than 100 nm, and more preferably more than 200 nm.

[0129] The ridge width (waveguide width) is preferably 3 μm or less, more preferably 2 μm or less. The ridge width is preferably 0.5 μm or more, more preferably 1 μm or more.

[0130] The thickness of waveguide 15 (excluding the thickness of the substrate) is preferably 15 μm or less, more preferably 10 μm or less, and even more preferably 7 μm or less. The lower limit of the thickness of waveguide 15 is not particularly limited, but is preferably 5 μm or more. Thus, in this embodiment, the waveguide can also be made into a thin film.

[0131] Figure 4 yes Figure 2 The top view of the waveguide shown is a schematic diagram visualizing the waveguide pattern. For example... Figure 4 As shown, in a waveguide, laser light is input to the waveguide end face, and the intensity of the laser light emitted from the opposite side of the waveguide is measured. This allows the determination of the input and output losses relative to the waveguide length. Then, by plotting the input and output losses relative to each waveguide length and calculating the slope, the optical propagation loss can be determined. Figure 5 ).

[0132] (Optical modulator)

[0133] This embodiment relates to an optical modulator using the aforementioned waveguide. That is, the optical modulator in this embodiment is a waveguide-type optical modulator. Such optical modulators are used in optical waveguide devices, optical communication devices, and the like.

[0134] The optical modulator in this embodiment may, for example, have... Figure 6 The structure shown. As shown in the image. Figure 6 As shown, in addition to the waveguide described above, the optical modulator 100 also includes electrodes 50a and 50b. Electrodes 50a and 50b can be made of, for example, Au, Al, Cu, etc. Furthermore, multiple electrodes 50a and 50b are arranged such that they sandwich the waveguide, and the refractive index of the optical modulator changes by applying an electric field between a pair of electrodes.

[0135] The spacing between each electrode is preferably 3 μm or more, more preferably 5 μm or more, and even more preferably 6 μm or more. Furthermore, the spacing between each electrode is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 7 μm or less. By making the spacing between each electrode within the above range, the modulation voltage input to the electrodes can be applied to the waveguide section efficiently.

[0136] Figure 6 Electrode 50b is a ground electrode, and an electrical signal is input to electrode 50a at a predetermined voltage. By inputting laser light to the waveguide end face and measuring the light intensity of the laser light emitted from the opposite side of the waveguide, the half-wavelength voltage (Vπ), which is an indicator of the operating voltage of the optical modulator, can be measured. When measuring using a laser source with a wavelength of 1550 nm, the half-wavelength voltage (Vπ) of the optical modulator is preferably 10 V or less, more preferably 5 V or less, and even more preferably 3 V or less. It should be noted that the lower limit of the half-wavelength voltage (Vp) is not particularly limited, but for example, it is preferably 0.0001 V or more. Furthermore, when measuring using a laser source with a wavelength of 1310 nm, the half-wavelength voltage (Vπ) of the optical modulator is preferably 10 V or less, more preferably 5 V or less, and even more preferably 3 V or less. It should be noted that the lower limit of the half-wavelength voltage (Vp) is not particularly limited, but for example, it is preferably 0.0001 V or more. Furthermore, in this embodiment, the electro-optic coefficient obtained from the half-wavelength voltage and the electrode structure (length, electrode spacing) is preferably 50 pm / V or more, more preferably 60 pm / V or more, even more preferably 80 pm / V or more, and particularly preferably 100 pm / V or more.

[0137] In this embodiment, the phase length (electrode length) of the optical modulator can be shortened, enabling miniaturization. For example, the phase length (electrode length) of the optical modulator including the structure of this embodiment is preferably 20 mm or less, more preferably 10 mm or less, further preferably 5 mm or less, still further preferably 4 mm or less, and particularly preferably 3 mm or less. By setting the phase length (electrode length) of the optical modulator within the above range, the decay of the high-frequency electrical signal input to the electrode can be effectively suppressed.

[0138] In this embodiment, a large electro-optic coefficient can be obtained in the optical modulator, so an optical modulator that can operate at high speed can be fabricated. For example, when an optical modulator is fabricated using the structure of this embodiment, optical modulation of 40 Gbit / s or more, 50 Gbit / s or more, 60 Gbit / s or more, 70 Gbit / s or more, 80 Gbit / s or more, 90 Gbit / s or more, and even 100 Gbit / s or more can be achieved. It should be noted that the accuracy of the optical modulation signal can be evaluated by the shape of the eye diagram of the optical modulation signal and the Q value defined by the amplitude and signal noise of the signal. For example, the Q value defined by the amplitude and signal noise of the signal is preferably 3.5 or more, more preferably 4.0 or more, further preferably 4.5 or more, and particularly preferably 5.0 or more.

[0139] In this embodiment, even if the voltage between the electrodes is reduced, the refractive index of the optical modulator can be controlled with good accuracy. Thus, the optical modulator of this embodiment is an optical modulator that can operate at low voltage and high speed. In addition, in the optical modulator of this embodiment, a high electro-optic effect can be obtained, so it is highly efficient and enables ultra-high-speed modulation.

[0140] Examples

[0141] Examples and comparative examples are given below to more specifically illustrate the features of the present invention. The materials, amounts used, ratios, processing contents, processing sequences, etc. shown in the following examples can be appropriately changed as long as they do not depart from the gist of the present invention. Therefore, the scope of the present invention should not be construed as being limited by the specific examples shown below.

[0142] (Example 1)

[0143] <Preparation of PZT Solution>

[0144] Measure lead acetate trihydrate (2.87 g) and perform vacuum drying at 105 °C for dehydration.

[0145] Measure tetra-isopropyl titanate (2.29 g) and zirconium butoxide (0.795 g), add 3.085 g of acetylacetone, mix for 30 minutes to prepare a mixed solution. Mix the thus obtained mixed solution with 15 ml of 2-methoxyethanol (solution a).

[0146] Dropwise add solution a to dehydrated lead acetate trihydrate and mix. Then, reflux at 90 °C for 2 hours and cool to room temperature. Next, add 2-methoxyethanol to make it 0.4 M and let it stand for 24 hours. Thus, a PZT solution is obtained.

[0147] <Preparation of seed layer solution>

[0148] Mix 0.311 g of lanthanum nitrate hexahydrate and 20 ml of 2-methoxyethanol and stir to obtain a seed layer solution. The seed layer solution is diluted in a ratio of seed layer solution:2-methoxyethanol = 2:1 (weight ratio) immediately before film formation.

[0149] In addition, mix 0.05 g of polyvinylpyrrolidone (PVP) and 20 ml of 2-methoxyethanol and stir to obtain a PVP solution.

[0150] <Formation of seed layer>

[0151] Prepare a silicon substrate with a thermal oxide film (SiO2 / Si substrate) cut into a 20 mm × 20 mm square as the substrate. The film thickness of the thermal oxide film is 3 μm, and the thickness of the silicon substrate is 525 μm. Spin-coat a PVP (polyvinylpyrrolidone) solution on the thermal oxide film of the above substrate at 4000 rpm / 1 minute, and then spin-coat a seed layer solution diluted with 2-methoxyethanol at 4000 rpm / 1 minute, and heat at 300 °C in the air for 5 minutes. Further spin-coat a PVP solution on it at 4000 rpm / 1 minute, and then spin-coat a seed layer solution diluted with 2-methoxyethanol at 4000 rpm / 1 minute, and heat at 300 °C in the air for 5 minutes. Then, heat at 500 °C in the air for 15 minutes to form a seed layer with a thickness of about 10 nm.

[0152] <Film formation of PZT film>

[0153] Spin-coat the PZT solution on the seed layer at 4000 rpm / 1 minute and heat at 300 °C in the air for 5 minutes, and repeat this operation 8 - 9 times. Then, heat at 550 °C in an oxygen atmosphere for 15 minutes. Thus, a PZT film with a film thickness of about 800 nm is formed on the seed layer as a structure. Figure 11 is the XRD diffraction pattern of the PZT film.

[0154] Using the structure obtained in Example 1, a ridge waveguide was fabricated by the following method, and the optical propagation loss was evaluated by the light transmittance with respect to the waveguide length. As a result, the optical propagation loss of the ridge waveguide using the structure of Example 1 was 0.57 dB / mm.

[0155] (Example 2)

[0156] <Preparation of PLZT Solution>

[0157] Weigh out lead acetate trihydrate (2.87 g) and lanthanum acetate monohydrate (0.202 g) separately, and perform vacuum drying at 105 °C to dehydrate. Take 15 ml of 2-methoxyethanol as the solvent, and mix the vacuum-dried lead acetate trihydrate and lanthanum acetate monohydrate. Then, stir at 124 °C for 4 hours and let it stand at 100 °C for 2 hours. Thereby, the solvent is distilled off, and the temperature is lowered to 90 °C (Solution A).

[0158] Measure tetra-isopropyl orthotitanate (2.29 g) and zirconium butoxide (0.795 g), add 3.085 g of acetylacetone, and mix for 30 minutes to prepare a mixed solution. Mix the thus-obtained mixed solution with 15 ml of 2-methoxyethanol (Solution B).

[0159] Dropwise add Solution B to the above-obtained Solution A and mix. Then, perform reflux at 90 °C for 2 hours and cool to room temperature. Next, add 2-methoxyethanol to make it 0.4 M and let it stand for 24 hours. Thus, the PLZT solution is obtained.

[0160] <Formation of Seed Layer> [[ID=二十]]

[0161] A seed layer was formed on the substrate by the same method as in Example 1.

[0162] <Film Formation of PLZT>

[0163] Instead of using the PZT solution, the PLZT solution was used, and a PLZT film was formed as a structure by the same method as in Example 1 except for this point. Figure 12 is the XRD diffraction pattern of the PLZT film.

[0164] The optical propagation loss of the ridge waveguide using the structure obtained in Example 2 was calculated, and as a result, the optical propagation loss was calculated to be 0.50 dB / mm.

[0165] (Comparative Example 1)

[0166] <Formation of Seed Layer>

[0167] A titanium seed layer is formed on a silicon substrate with a thermal oxide film (silicon dioxide) (SiO2 / Si substrate) used in Example 1. When forming the titanium seed layer, titanium is vacuum-evaporated by a heating-type vacuum evaporation method to form a titanium seed layer with a thickness of 5 nm.

[0168] <Film formation of PLZT film>

[0169] Using the same method as in Example 1, a PLZT film is formed on the titanium seed layer to obtain a structure. It should be noted that, as Figure 1 shown, a large number of cracks are confirmed to form on the surface of the PLZT thin film formed on the titanium seed layer.

[0170] Using the structure obtained in Comparative Example 1, a ridge waveguide is fabricated by the method described later, and the optical propagation loss is evaluated by the transmittance relative to the waveguide length. As a result, the optical propagation loss of the ridge waveguide using the structure of Comparative Example 1 is 1.50 dB / mm.

[0171] (Evaluation and measurement)

[0172] (Evaluation of optical propagation loss)

[0173] <Fabrication of waveguide>

[0174] On the PZT film or PLZT film of the structures obtained in the examples and comparative examples, a linear waveguide pattern is formed using an electron beam resist and an electron beam lithography apparatus. Specifically, on the PZT film or PLZT film of the structure, an electron beam resist (RP6200 manufactured by ALLRESIST) and an electron beam lithography apparatus (G100 manufactured by ELIONIX) are used to fabricate a resist pattern for the linear waveguide ( Figure 3 (b)). In the waveguide pattern, the ridge lengths are 2 mm, 4 mm, 6 mm, and 8 mm respectively, the ridge height is 100 nm, and the ridge width is 3 μm. Using a RIE dry etching apparatus (RIE-10NR manufactured by Samco, CHF3 / Ar mixed gas, 1.8 Pa), the PZT film or PLZT film is etched to form Figures 2-4 a linear waveguide pattern as shown. Figure 2 is a cross-sectional view in the width direction of the waveguide (a cross-sectional view in the direction perpendicular to the direction in which the waveguide pattern extends). In Figure 2 , the ridge height is represented by h, and the ridge width is represented by w. Figure 3 is a top view of the waveguide, which is a schematic diagram visualizing the waveguide pattern. In Figure 3 , the ridge length is represented by h. After that, the electron beam resist is removed by oxygen etching ( Figure 3(c) Next, a top cladding layer with a maximum thickness of approximately 1 μm was formed using polymethyl methacrylate (PMMA) resin as the ridge waveguide 10. Figure 3 (d)). In Figure 2 In this context, the maximum thickness of the PMMA layer is represented by t.

[0175] Measurement of light propagation loss

[0176] like Figure 4 As shown, a laser source 20 with a wavelength of 1550 nm and an optical fiber 25 are used to input laser light into the waveguide end face. An objective lens 30 is used to focus the laser light emitted from the opposite side of the waveguide, and an optical power meter 40 is used to measure the light intensity. The input laser intensity is fixed at 10 dBm. The ratio of the output laser intensity to the input laser intensity (input-output loss) is calculated for waveguides with different ridge lengths (2, 4, 6, 8 mm). The input-output loss values ​​relative to each waveguide length are plotted. Figure 5 The slope of the input and output loss values ​​relative to each waveguide length is taken as the optical propagation loss.

[0177] [Table 1]

[0178]

[0179] Based on the above results, a waveguide was fabricated using the structure obtained in Example 1, and the optical propagation loss was calculated to be 0.57 dB / mm. In Example 2, the optical propagation loss was calculated to be 0.50 dB / mm. Furthermore, in these examples, a uniform PZT thin film or PLZT thin film with excellent crystal orientation could be formed on the amorphous film.

[0180] On the other hand, in Comparative Example 1, a PLZT thin film was formed by vacuum evaporation of a 5 nm thick titanium seed layer on a SiO2 / Si substrate. The light transmittance evaluation showed a light propagation loss of 1.5 dB / mm. Furthermore, numerous cracks were observed on the surface of the PLZT thin film formed on the titanium seed layer. Figure 7 Thus, in Comparative Example 1, it was impossible to form a good PLZT film on the amorphous film.

[0181] (Evaluation of electro-optic coefficient)

[0182] <Fabrication of an Optical Modulator>

[0183] Optical modulator 100 used Figure 6 The general Mach-Zehnder interferometer waveguide structure shown is fabricated. Figure 6The Mach-Zehnder interferometer waveguide structure shown is a Y-shaped branched waveguide structure with light intensity branched in a 1:1 ratio. This Mach-Zehnder interferometer waveguide structure is formed by the following method: First, on the PZT or PLZT film of the structures obtained in the embodiments and comparative examples, an electron beam resist pattern for the Y-branched waveguide is fabricated using an electron beam resist and an electron beam tracing apparatus (ELIONIX, G100). Electrodes 50a and 50b are arranged to clamp the Y-branched waveguide, with an electrode length of 4 mm, an electrode width of 20 mm, and an electrode spacing of 8 mm. The PZT or PLZT film is etched using a RIE dry etching apparatus (Samco, RIE-10NR, CHF3 / Ar mixed gas, 1.8 Pa) to form the Y-branched waveguide pattern.

[0184] On a PZT or PLZT film with a waveguide pattern, 50 nm of titanium is deposited using a heated vacuum evaporation method, followed by 1 μm of aluminum. Then, the electron beam resist is removed by oxygen etching. Next, a top cladding layer with a maximum thickness of approximately 1 μm is formed using polymethyl methacrylate (PMMA) resin, thus fabricating the optical modulator 100.

[0185] <Optical Modulation Evaluation>

[0186] For the fabricated optical modulator, half-wavelength voltage was evaluated using laser sources with wavelengths of 1550 nm and 1310 nm. The laser polarization wave was TE deflected and input to the optical modulator using a polarization-maintaining fiber. The modulation voltage (10 Vpp, 10 kHz) was input to electrode 50a using a function generator 52. Electrode 50b served as a ground electrode. The output light from the optical modulator was incident on an optical fiber and connected to a photodetector 60. The intensity of the emitted light detected by the photodetector 60 was evaluated using an oscilloscope 70. Figure 8 The results of analyzing the optical modulation characteristics using an oscilloscope are shown. In addition to the signal from the photodetector 60, the oscilloscope also receives a voltage signal from the function generator 52, which is displayed simultaneously with the optical signal. The half-wavelength voltage (Vπ) is used as an indicator of the operating voltage of the optical modulator. Vπ is defined as the voltage required for a 180° electro-optic phase shift. Figure 8 As shown in (a) and (b), the half-wavelength voltage of the PZT modulator using the structure of Example 1 is Vπ = 3.2V (wavelength 1550nm) and Vπ = 2.5V (wavelength 1310nm), as... Figure 8 As shown in (c) and (d), the half-wavelength voltage of the PLZT modulator using the structure of Example 2 is Vπ = 2.2V (wavelength 1550nm) and Vπ = 1.2V (wavelength 1310nm).

[0187] The phase length (electrode length) of the fabricated optical modulator is 4 mm. The half-wavelength voltage is inversely proportional to the phase length; therefore, the VπL value, obtained by multiplying the half-wavelength voltage by the phase length, serves as an indicator of the half-wavelength voltage characteristic relative to the phase length. The VπL values ​​for the PZT modulator are 1.3 Vcm (wavelength 1550 nm) and 1.0 Vcm (wavelength 1310 nm), while those for the PLZT modulator are 0.883 Vcm (wavelength 1550 nm) and 0.48 Vcm (wavelength 1310 nm).

[0188] [Table 2]

[0189]

[0190] Lithium niobate is one example of a material currently used in practical optical modulators, and lithium niobate modulators are widely used in optical fiber communication. According to various literature reports, including VπL = 6.7Vcm (PO Weigel, et al. Optics Express 26(18), 23728(2018)), VπL = 2.7Vcm (M. He, et al. Nature Photonics 13, 359(2019)), and VπL = 2.2Vcm (G. Chen, et al. APL Photonics 7(2), 026103(2022)), it can be seen that the PZT modulator and PLZT modulator in this embodiment have excellent operating voltage characteristics. Furthermore, the electro-optic coefficients calculated from the half-wavelength voltage and electrode structure (length, electrode spacing) are 86 pm / V for PZT and 198 pm / V for PLZT. The electro-optic coefficient of lithium niobate is 31 pm / V, thus confirming that PZT and PLZT have large electro-optic coefficients.

[0191] It should be noted that in the structure of Comparative Example 1, a large number of cracks were formed on the surface of the PLZT film, making it impossible to evaluate the electro-optic coefficient.

[0192] (Evaluation of High-Speed ​​Optical Modulation)

[0193] Using the structure created in Example 1, fabricate... Figure 9 The optical modulator 100 shown is used for high-speed optical modulation experiments. An arbitrary signal generator 54 is used to input an NRZ electrical signal from the optical input side to electrode 50a, and electrode 50b is grounded. Additionally, a 50Ω terminator 56 is installed on the optical output side. The modulated light output from the optical fiber is amplified using an optical amplifier (EDFA) 80 and connected to a high-speed photodetector 82. The high-speed photodetector 82 is connected to a digital signal analyzer 84 to measure the eye diagram of the optical modulation signal. Figure 10Eye diagrams of 64 Gbit / s and 80 Gbit / s are shown. The opening of the signal representing the precision of the optical modulation signal is large, and a clear waveform is obtained. In addition, the Q value defined by the amplitude of the signal and the signal noise is 10.1 at 64 Gbit / s and 5.6 at 80 Gbit / s. The Q value related to the signal precision is preferably 3.5 or more, and the obtained Q value is a sufficiently large value. As a high-speed optical modulator using a PZT thin film, there is a literature (Koen Alexander, et al. Nature Communications 9, 3444 (2018)), and an optical modulation of up to 40 Gbit / s has been obtained. It can be seen that the optical modulation characteristics obtained in this embodiment can greatly achieve high speed.

[0194] It should be noted that in the optical modulator using the structure of this embodiment, high-speed signal transmission of 100 Gbit / s can also be performed. By using a multi-level modulation method (2 bits), transmission of 200 Gbit / s has also been confirmed.

[0195] (Example 3)

[0196] (Formation of seed layer)

[0197] A seed layer is formed on the substrate by the same method as in Example 1.

[0198] (Film formation of BTO thin film)

[0199] A BTO solution (manufactured by Mitsubishi Materials Corporation) is spin-coated on the seed layer at 2000 rpm for 1 minute. Then, it is heated at 700 °C for 15 minutes in an oxygen atmosphere. In this way, a BTO film with a film thickness of about 100 nm is formed on the seed layer as a structure. Figure 13 This is the XRD diffraction pattern of the BTO film. Peaks corresponding to the (110), (111), and (211) orientations are confirmed at 31.5°, 38.9°, and 56.1°.

[0200] (Example 4)

[0201] (Preparation of PZT solution)

[0202] A PZT solution is prepared by the same method as in Example 1.

[0203] (Formation of seed layer)

[0204] A seed layer is formed on the substrate by the same method as in Example 1.

[0205] (Film formation of PZT thin film)

[0206] The diluted PZT solution was spin-coated on the seed layer at 4000 rpm for 1 minute and heated at 300 °C for 5 minutes in the atmosphere. Then, it was heated at 550 °C for 15 minutes in an oxygen atmosphere. Thus, a PZT thin film was formed on the seed layer.

[0207] <Formation of BTO thin film>

[0208] The BTO solution (manufactured by Mitsubishi Materials Corporation) was spin-coated on the PZT thin film formed on the seed layer at 2000 rpm for 1 minute. Then, it was heated at 700 °C for 15 minutes in an oxygen atmosphere. Thus, a BTO film with a thickness of about 100 nm was formed on the seed layer as a structure. Figure 14 It is the XRD diffraction pattern of the BTO film. The diffraction peaks at 22.2° and 45.3° correspond to the (100) and (200) orientations, respectively, and it can be confirmed that the BTO is an oriented crystal film.

[0209] Symbol Explanation

[0210] 2 Substrate

[0211] 4 Seed layer

[0212] 6 Ferroelectric thin film

[0213] 8 Top cladding

[0214] 10 Structure

[0215] 12 Resist

[0216] 14 Ridge

[0217] 15 Waveguide

[0218] 20 Laser

[0219] 25 Optical fiber

[0220] 30 Objective lens

[0221] ​​​​​​​​​​​​​​​​​​​​​​​​84 High-speed photodetector

[0230] 86 Digital Signal Analyzer

[0231] 100 optical modulator

Claims

1. A structure having: A substrate made of amorphous material; A seed layer deposited on the substrate; and PZT film, PLZT film, BTO film or BSTO film deposited on the seed layer in, When the optical propagation loss is calculated using the following measurement method, the optical propagation loss is less than 1 dB / mm. Measurement method: Waveguide patterns with ridge lengths of 2mm, 4mm, 6mm, and 8mm, ridge height of 100nm, and ridge width of 3μm are formed on the structure. A 1μm thick upper cladding layer is formed on the waveguide pattern using polymethyl methacrylate resin, serving as the waveguide. A 1550nm wavelength laser source and optical fiber are used to input laser light into the waveguide end face. An objective lens is used to focus the laser light emitted from the opposite side of the waveguide, and an optical power meter is used to measure the light intensity. The input laser intensity is fixed at 10dBm. The ratio of the output laser intensity to the input laser intensity in waveguides with different waveguide lengths is calculated, i.e., the input-output loss. The slope of the input-output loss relative to the waveguide length is calculated as the optical propagation loss.

2. The structure according to claim 1, wherein, The seed layer contains lanthanum nitrate as its main component.

3. A structure having: A substrate made of amorphous material; A seed layer deposited on the substrate; and PZT film, PLZT film, BTO film or BSTO film deposited on the seed layer The seed layer contains lanthanum nitrate as its main component.

4. The structure according to claim 1 or 3, wherein, The thickness of the seed layer is less than 15 nm.

5. The structure according to claim 1 or 3, wherein, The substrate is a silicon substrate.

6. The structure according to claim 5, wherein, The silicon substrate has a thermal oxide film.

7. The structure according to claim 1 or 3, wherein, The PZT film, PLZT film, BTO film or BSTO film deposited on the seed layer also has a PZT film, PLZT film, BTO film or BSTO film.

8. A waveguide comprising the structure of claim 1 or 3.

9. An optical modulator formed by forming electrodes in a structure as described in claim 1 or 3.

10. A method for manufacturing a structure, which is the method for manufacturing the structure according to claim 1, comprising: The process of forming a seed layer on a substrate made of an amorphous material; and The process of forming a PZT thin film, PLZT thin film, BTO thin film or BSTO thin film on the seed layer.

11. The method for manufacturing the structure according to claim 10, wherein, Prior to the process of forming the seed layer, the process also includes a process of coating a hydrophilic polymer content onto the substrate.

12. A method for manufacturing a structure, comprising: The process of coating a hydrophilic polymer onto a substrate made of an amorphous material; The process of forming a seed layer on the surface of the substrate coated with the hydrophilic polymer inclusion; and The process of forming a PZT thin film, PLZT thin film, BTO thin film or BSTO thin film on the seed layer.

13. The method for manufacturing the structure according to claim 10 or 12, wherein, The seed layer contains lanthanum nitrate as its main component.

14. The method for manufacturing a structure according to claim 12, wherein, The hydrophilic polymer is polyvinylpyrrolidone.

15. The method for manufacturing the structure according to claim 10 or 12, wherein, The PZT film, PLZT film, BTO film, or BSTO film is formed by the sol-gel method.

16. The method for manufacturing a structure according to claim 10 or 12, wherein, The substrate is a silicon substrate.

Citation Information

Patent Citations

  • Light guide type optical control device

    JP1988221306A

  • Structure having light modulating film and optical controlling device using same

    WO2005015292A1